The Effect of Systemic Chemotherapy on Ovarian Function: A Prospective Clinical Trial - Duymaz, Tomris (Aves, 2020)
Objective: Premenopausal women with breast cancer arc at risk of developing ovarian failure after chemotherapy. The aim of this study was to investigate the negative effects of systemic chemotherapy on ovarian function in premenoupausal women with breast cancer. Materials and Methods: Thirty-one premenopausal women with operable breast cancer aged between 26-48 years were enrolled in this prospective cohort study CO investigate preliminary results. Additional 69 patients data will be included after the completion of all five measurements. The change in serum Antimullerian Hormone (AMH) levels, mean ovarian volumes (MOV) and antral follicle counts (AFCs) at 3-month intervals were recorded to evaluate ovarian function. Women who had at least one pretreatment and four post-treatment measurements in one year follow-up period were included in the study. Decision of chemotherapy regimen was taken by the Tumor Board. Results: Thirty-one patients had all five AMH, MOV and AFCs results. There was a statistically significant negative correlation between 1st - 5th AMH levels (p=0.006) and 1st - 5th AFCs during the follow-up period (p<0.0001). However pie- and post-chemotherapy measurements of MOVs did not demonstrate any significant correlation (p=0.799). BMI, parity, lactation, him pathology and molecular subtypes of breast cancer, alcohol intake, smoking and type of chemotherapy regimen were not significantly correlated with AMH, AFC and MOV. Conclusion: Pretreatment AMH levels and AFC were shown to have a significant role in early prediction of ovarian-reserve after chemotherapy.
8 pages
Keywords: Chemotherapy; Breast cancer; AMH; Ovarian reserve